Monitoring the flow rate of water in the supercritical convection loop - Bakai, A.S.; Biller, E.Z.; Bovda, A.M.; Boriskin, V.N.; Gorenko, Yu.V.; Momot, V.A.; Onischenko, L.V.; Solodovnikov, V.I.; Shelepko, S.V. (Вопросы атомной науки и техники, 2016)
The Supercritical Water Convection Loop with an irradiation chamber is created in KIPT. The Loop is made
from stainless steel. It measures 1.2 by 1.5 m. The plant makes possible to carry out simulation corrosion tests of
potential structural materials for Generation IV reactors with the Supercritical Water-Cooling (SCWR) under irradiation.
Specimens in water flow at 350…400°C, 23…25 MPa are irradiated by the 10 MeV/10 kW electron beam of
LUE-10 linear accelerator. The monitor with powerful permanent magnets in the turning components is being devised
for expeditious control of the flow water velocity. В ХФТИ создана сверхкритическая водяная конвекционная петля с камерой облучения. Петля размером
1,2х1,5 м изготовлена из нержавеющей стали. Установка позволяет проводить коррозионные тесты потенциальных конструкционных материалов реакторов IV поколения сверхкритическим водным охлаждением
под облучением. Образцы в потоке воды при 350…400°C, 23…25 МПа облучаются электронным пучком
10 МэВ/10 кВт линейного ускорителя ЛУЭ-10. Приводятся результаты разработки мониторов для контроля
скорости потока в сверхкритической водяной петле при облучении исследуемых материалов. У ХФТІ створена надкритична водяна конвекційна петля з камерою опромінення. Петля розміром
1,2х1,5 м виготовлена з нержавіючої сталі. Установка дозволяє проводити корозійні тести потенційних
конструкційних матеріалів реакторів ІV покоління надкритичним водним охолодженням під опроміненням.
Зразки в потоці води при 350...400°C, 23...25 МПа опромінюються електронним пучком 10 МеВ/10 кВт
лінійного прискорювача ЛПЕ-10. Наводяться результати розробки моніторів для контролю швидкості
потоку в надкритичній водяній петлі при опроміненні досліджуваних матеріалів.